Modifikasi Model Pembelajaran Experiential Learning untuk Meningkatkan Kemampuan Pedagogi Calon Guru - Setiono, Panut; Setyosari, Punaji; Praherdhiono, Henry; Harsiati, Titik; Amaliyah, Yuli (Fakultas Ilmu Pendidikan Universitas Negeri Padang, 2025)
This study presents a modified Experiential Learning (EL) model designed to improve the pedagogical competence of pre-service teachers. Building on Kolb’s framework, the revised model integrates structured learning objectives, reflective problem-solving strategies, and abstraction ontology to enhance metacognitive, creative, and metaliteracy skills. The model emphasizes authentic classroom engagement through active experimentation and guided reflection. Developed through a systematic literature review, it offers a structured and adaptable approach for teacher education programs. While the model demonstrates theoretical potential, further empirical testing is needed to validate its effectiveness in real-world settings. This innovation contributes to the development of experiential learning frameworks that align with contemporary educational demands.